Effectiveness of Audiovisual E-Module on the Behavior of Prospective Brides Regarding Preparation for Healthy Pregnancy - Sepriarum, Satyawati Narda; Rijanto; Setiyani, Astuti; Nurchandra, Domas (Universitas Nahdlatul Ulama Surabaya, 2025)
Prospective brides are the target group in efforts to improve pre-pregnancy health. Ahead of marriage, many prospective brides do not have enough information about reproductive health in the family, so that after marriage, pregnancy is often not well planned and not supported by good health status. The purpose of this study was to determine the effectiveness of audiovisual e-modules on the behaviour of prospective brides about healthy pregnancy preparation. This research is a quantitative study that uses a quasi-experimental design with a control group and a two-group pretest-posttest design. Samples were taken using the purposive sampling technique, obtaining a total of 32 respondents. The independent variable is education with audiovisual e-module media and leaflets. While the dependent variable is the behaviour of prospective brides about healthy pregnancy preparation. Data collection using a questionnaire. In analysing the effect of using the Wilcoxon Signed Rank Test using α = 0.05%. The results of the study showed that intervention through audiovisual e-module media was effective in improving the behavior of prospective brides and grooms related to healthy pregnancy preparation (p = 0.000). The Wilcoxon Signed Rank test proved that there was a significant change. Health education using audiovisual e-module media effectively influences bride-to-be behavior in preparing for a healthy pregnancy. Therefore, it is recommended to enhance reproductive health during the preconception period.